The National Lung Cancer Audit: The Impact of COVID-19. Issue 11 (November 2022) - Conibear, J.; Nossiter, J.; Foster, C.; West, D.; Cromwell, D.; Navani, N.
Abstract: Since 2014, the National Lung Cancer Audit (NLCA) has been evaluating the performance of the UK NHS lung cancer services against established standards of care. Prior to the onset of the COVID-19 pandemic, the NLCA's annual reports revealed a steady stream of improvements in early diagnosis, access to surgery, treatment with anti-cancer therapies, input from specialist nursing and survival for patients with lung cancer in the NHS. In January 2022, the NLCA reported on the negative impact COVID-19 has had on all aspects of the lung cancer diagnosis and treatment pathway within the NHS. This article details the fundamental changes made to the NLCA data collection and analysis process during the COVID-19 pandemic and details the negative impact COVID-19 had on NHS lung cancer patient outcomes during 2020.